A CONSTRUÇÃO DISCURSIVA E A RECEPÇÃO DA HOMOAFETIVIDADE NA TELEDRAMATURGIA BRASILEIRA: consumo, representação e identidade homossexual - Oliveira, José Aparecido de (2014)
This study aims to evaluate the representation and discourse of gay characters in Brazilian soap operas and their potential relationship with the demands of the homosexual community in their struggle for greater tolerance and emancipation. The methodology includes two analytical approaches: the first focuses on the field of production, from the assumptions of Discourse Analysis and Queer Studies, checking the textual aspects of discourse and representation of gay characters in soap operas. The second approach focuses on the field of circulation and consumption, by the assumptions of Reception Studies, in order to assess how the receivers perform the appropriation of discourse and representation of homosexual soap opera. This second approach has a quantitative instrument and a semistructured qualitative interview, applied to a sample of 402 participants, heterosexual and homosexual, mostly young graduate students in Belo Horizonte, MG. As for discourse analyzes, the results demonstrate a change in the pattern of representation of gay characters, moving the heteronormative for a more humanized standard representation, following the historical moment of political maturity of society and the introduction of legal frameworks favorable to homosexual subjects. As for Reception Studies, the results confirm the pedagogical potential of the soap opera to broaden the discussion on homoaffective question; assist the gay guy to accept his sexual identity and encourage him to disclose his sexual orientation.